ANALISIS KESESUAIAN LAYANAN PEMBIAYAAN BERBASIS TEKNOLOGI INFORMASI YANG BERPRINSIP SYARIAH DENGAN FATWA DSN-MUI NO.117/DSN-MUI/II/2018 (Studi pada PT. Alami Sharia) - Putra, Muhammad Daffa Raka; Puspita (Journal of Accounting, Management and Islamic Economics, 2025)
This study aims to discuss the analysis of the suitability between information technology-based loan services using Sharia principles and DSN-MUI Fatwa No. 117/DSN-MUI/II/2018. The research focuses on research in one of the technology-based loan service providers with Sharia principles, namely PT. Alami Sharia. The method used is a method with a qualitative-descriptive approach with data collection techniques in the form of interviews and with validity techniques in the form of triangulation of data sources. The results of this analysis are information technology-based loan services with Sharia principles carried out by PT. Alami Sharia is following what is stated in the DSN-MUI fatwa No. 117/DSN-MUI/II/2018.